EFFICACY OF TRATAKA IN IMPROVEMENT OF VISION IN MYOPIC AND HYPERMETROPIC CHILDREN - Badwaik Premkumar Panjabrao (International Journal of Applied Ayurved Research, 2016)
Numbers of children are suffering from myopia and hypermetropia due to excess use of computers, T.V.sets, mobiles etc. so it is the need of the hour to protect and save the eyes from these types of refractive errors. Trataka is one of Shatkriya which is very useful in eye disorders. It is good for vision. To study the efficacy of Trataka two groups i.e., myopic and hypermetropic between the ages of 13 to 16 yrs are selected for this study. After completion of 3 months study it has been observed that in myopic group it was observed that Diminished Ophthalmic Vision is reduced to 90%. Headache is reduced by 66.67%, lacrimation of eyes is reduced to 84.62%, ocular pain is decreased up to 85.71% & eye fatigue is reduced by 65.22%. In hypermetropic group of children it was observed that Diminished Ophthalmic Vision is reduced to 48.78%, headache is reduced to 69.56%, lacrimation of eyes is cured up to 56.25%, ocular pain is reduced to 61.90% and eye fatigue is reduced to 63.15%. So Trataka plays an important role in Myopia and Hypermetropia in children. It can be recommended to minimize the refractive error.